Double-sided adhesive sheet, laminate and display device
The double-sided adhesive sheet, formulated with a specific photocurable composition, addresses the issue of copper mesh visualization in touch panels by enhancing oxygen permeability and maintaining excellent visibility and design.
Patent Information
- Application Number
- JP2023084165
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-05-22
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2043-05-22
AI Technical Summary
Conventional adhesive sheets fail to suppress visualization of copper meshes when laminated to transparent conductive copper films, especially under high temperature environments, which affects the visibility and design of touch panels.
A double-sided adhesive sheet is developed using a photocurable adhesive composition containing a (meth)acrylic copolymer, specific monomers, and a photopolymerization initiator, which achieves high oxygen permeability and suppresses visualization of the copper mesh.
The adhesive sheet effectively prevents visualization of the copper mesh even when laminated to transparent conductive copper films, ensuring excellent visibility and design for display devices.
Smart Images

Figure 0007663103000003 
Figure 0007663103000001 
Figure 0007663103000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a double-sided pressure-sensitive adhesive sheet, a laminate, and a display device. [Background technology]
[0002] In recent years, display devices such as liquid crystal displays (LCDs) and input devices such as touch panels have been widely used in various fields. Touch panels are of various types, such as resistive film type and capacitive type, but the capacitive type is mainly used. In the manufacture of display devices equipped with these touch panels, transparent adhesive sheets are used to bond optical members, for example, transparent adhesive sheets are used to bond display devices and input devices.
[0003] Traditionally, metal oxides such as ITO (indium tin oxide) have been widely used for the transparent conductive film of touch panels. ITO is a transparent and conductive material, but it is known that its conductivity is inferior to that of metals such as copper. For example, when ITO is used for the transparent conductive film of a large-screen touch panel sensor, there are cases where the detection accuracy cannot be maintained, which has been an issue. For this reason, the use of a metal mesh such as copper for the transparent conductive film of a touch panel is being considered.
[0004] However, since a metal mesh such as copper has a metallic luster, the copper mesh (copper wiring) becomes visible by reflecting external light, which reduces the transparency of the transparent conductive film and reduces the visibility and design of the touch panel. For this reason, it has been considered to suppress reflection by superposing a blackening film on the copper mesh. For example, Patent Document 1 discloses a conductive laminate for a touch panel, which includes a light-transmitting substrate, a light-transmitting underlayer, a first copper oxynitride layer located on the underlayer opposite to the substrate, a copper layer located on the first copper oxynitride layer opposite to the underlayer, and a second copper oxynitride layer located on the copper layer opposite to the first copper oxynitride layer. Patent document 2 discloses a method for manufacturing a touch panel sensor, which comprises the steps of: preparing a double-sided film material by bonding a first single-sided film material having a metal layer and a blackened metal layer in that order on one main surface of the film substrate, and a second single-sided film material having a blackened metal layer and a metal layer in that order on one main surface of the film substrate, via an adhesive or bonding agent; simultaneously etching the metal layers of the double-sided film material by a photolithography method using double-sided exposure to form a metal wiring pattern all at once; and bonding a cover glass to the blackened metal layer side via an adhesive or bonding agent, and bonding the film substrate to the metal layer side. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2016 / 136117 [Patent Document 2] JP 2015-125563 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, the inventors' investigations revealed that when a conventional adhesive sheet is attached to a transparent conductive film having a copper mesh overlaid with a blackened film and the film is placed in a high-temperature environment, for example, the hue of the blackened film changes and the copper mesh becomes visible.
[0007] Therefore, in order to solve such problems of the conventional technology, the inventors conducted research with the aim of providing an adhesive sheet that can suppress the visualization of copper mesh even when the adhesive sheet is attached to a copper mesh-based transparent conductive film. [Means for solving the problem]
[0008] Examples of specific embodiments of the present invention are given below. [1] A (meth)acrylic copolymer (A), a monofunctional (meth)acrylic acid ester monomer (B1) having a linear, branched or cyclic alkyl group having 10 to 20 carbon atoms; a bifunctional (meth)acrylic acid ester monomer (B2) having a reactive functional group linked via a linking group derived from a linear diol having 4 to 12 carbon atoms; A double-sided pressure-sensitive adhesive sheet obtained by photocuring a pressure-sensitive adhesive composition containing a photopolymerization initiator (C) other than a hydrogen abstraction type polymerization initiator, The oxygen permeability (P) of the double-sided adhesive sheet was measured and calculated using the following method. A ) is 2000ml / (m 2 ·1day·1atm) or higher, double-sided adhesive sheet; (Measurement method) The thickness of the double-sided pressure-sensitive adhesive sheet was set to 200 μm, and a 20 μm-thick unstretched polypropylene film (CPP) was attached to each side of the sheet to produce a laminated sheet with a layer structure of "CPP (20 μm) / double-sided sheet (adhesive layer 200 μm) / CPP (20 μm)". The oxygen transmission rate of the laminated sheet was measured using an oxygen transmission rate measuring device under an environment of 23°C, relative humidity 50%, and 1 atm. 2 The oxygen permeability of the laminated sheet (P LSimilarly, the oxygen permeability (P P ) and the oxygen permeability (P A ) is calculated. 1 / P L =1 / P A +1 / P P ··· Equation (1) P A =(P P ×P L ) / (P P -P L )...Equation (2) [2] The double-sided pressure-sensitive adhesive sheet according to [1], wherein the (meth)acrylic copolymer contains (a1) a unit derived from an acrylate having a linear or branched alkyl group having 1 to 10 carbon atoms, (a2) a unit derived from a methacrylate having a linear or branched alkyl group having 1 to 10 carbon atoms, and (a3) a unit derived from a hydroxyl group-containing (meth)acrylate. [3] The double-sided pressure-sensitive adhesive sheet according to [1] or [2], wherein the content of the monofunctional (meth)acrylic acid ester monomer (B1) is 0.1 to 10 parts by mass, and the content of the bifunctional (meth)acrylic acid ester monomer (B2) is 0.05 to 5 parts by mass, relative to 100 parts by mass of the (meth)acrylic copolymer (A). [4] The double-sided pressure-sensitive adhesive sheet according to any one of [1] to [3], which has a total light transmittance of 80% or more. [5] The double-sided pressure-sensitive adhesive sheet according to any one of [1] to [4], which has a gel fraction of 75 mass % or less. [6] A laminate comprising the double-sided pressure-sensitive adhesive sheet according to any one of [1] to [5] and a copper mesh-based transparent conductive film. [7] A display device comprising the double-sided pressure-sensitive adhesive sheet according to any one of [1] to [5] and a copper mesh-based transparent conductive film. Effect of the Invention
[0009] According to the present invention, even when an adhesive sheet is attached to a copper mesh-based transparent conductive film, the copper mesh can be prevented from becoming visible. This makes it possible to manufacture a display device with excellent visibility and design. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a schematic diagram showing an example of a cross-sectional configuration of a double-sided pressure-sensitive adhesive sheet of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in detail below. The following description of the constituent elements may be based on a representative embodiment or specific example, but the present invention is not limited to such an embodiment. In this specification, a numerical range expressed using "~" means a range including the numerical values before and after "~" as the lower and upper limits. In this specification, "(meth)acrylate" means acrylate or methacrylate.
[0012] (Double-sided adhesive sheet) The present invention relates to a double-sided pressure-sensitive adhesive sheet obtained by photocuring a pressure-sensitive adhesive composition comprising: (A) a (meth)acrylic copolymer; (B1) a monofunctional (meth)acrylic acid ester monomer having a linear, branched or cyclic alkyl group having 10 to 20 carbon atoms; (B2) a bifunctional (meth)acrylic acid ester monomer having a reactive functional group linked via a linking group derived from a linear diol having 4 to 12 carbon atoms; and (C) a photopolymerization initiator other than a hydrogen abstraction polymerization initiator. The oxygen permeability of the double-sided pressure-sensitive adhesive sheet, measured and calculated according to the following measurement method, is 2000 ml / (m 2 ·1day·1atm) or higher. (Measurement method) The thickness of the double-sided PSA sheet was set to 200 μm, and a 20 μm-thick unstretched polypropylene film (CPP) was attached to each side of the sheet to produce a laminated sheet with a layer structure of "CPP (20 μm) / double-sided PSA sheet (adhesive layer 200 μm) / CPP (20 μm)". The oxygen transmission rate of the laminated sheet was measured using an oxygen transmission rate measuring device under an environment of 23°C, relative humidity 50%, and 1 atm. 2 The oxygen permeability of the laminated sheet (P L Similarly, the oxygen permeability (P P ) was calculated, and the oxygen permeability (P A ) is calculated. 1 / P L =1 / P A +1 / P P ··· Equation (1) P A =(P P ×P L ) / (P P -P L )...Equation (2)
[0013] When preparing a laminated sheet with a layer structure of "unstretched polypropylene (thickness 20 μm) / adhesive layer (thickness 200 μm) / unstretched polypropylene (thickness 20 μm)", a 20 μm unstretched polypropylene (Rensol GP-32, manufactured by Hokuetsu Kasei Co., Ltd.) is laminated to both sides of a 200 μm thick double-sided adhesive sheet using a hand roller to prepare a laminated sheet. The oxygen permeability (P L ) is measured using an oxygen permeability measuring device. Next, the oxygen permeability (P P The oxygen permeability (P L ) and oxygen permeability of unstretched polypropylene film (P P) and the oxygen permeability (P A The oxygen permeability (P A ) is the sheet area of 1m 2 It represents the amount of oxygen that permeates a double-sided adhesive sheet (adhesive layer) per 24 hours (one day) under a pressure of 1 atm (=1 atmosphere). When measuring oxygen permeability using an oxygen permeability measuring device, the amount of oxygen permeated is measured in an environment of 23°C, relative humidity 50%, and 1 atm, using the measurement area specified by the device. Then, from the measured amount of oxygen, 2 The oxygen permeability is calculated by converting the amount of oxygen transmitted over 24 hours. For the measurement of oxygen permeability, it is preferable to use an oxygen permeability measuring device conforming to ASTM F2622. For example, an oxygen permeability measuring device (OX-TRAN2 / 12 manufactured by MOCON) can be used. When this device (OX-TRAN2 / 12) is used, the measurement area (test cell area) is 50 cm. 2 It can be measured by.
[0014] The oxygen permeability (P A ) is 2000ml / (m 2 ·1day·1atm) or more is sufficient, and 2050ml / (m 2 ·1day·1atm) or more is more preferable, and 2100ml / (m 2 1day 1atm) or more, and 2150ml / (m 2 The upper limit of the oxygen permeability is not particularly limited, but is preferably 30,000 ml / (m 2 In the present invention, the oxygen permeability (P A) is deliberately increased to a predetermined value or higher, it is possible to suppress the reduction of the components constituting the blackened film laminated on the copper mesh, and it is presumed that this makes it possible to suppress discoloration of the blackened film. As a result, it is possible to suppress visualization of the copper mesh. In this embodiment, the oxygen permeability (P A ) is achieved.
[0015] In this embodiment, the oxygen permeability (P A By setting the above range, for example, the amount of oxygen present in the vicinity of the blackened film of the copper mesh can be made to be equal to or greater than a certain amount. In this case, it is presumed that the extraction and reduction of oxygen in the blackened film can be suppressed, and discoloration can be suppressed.
[0016] The double-sided pressure-sensitive adhesive sheet of the present embodiment is preferably composed of only a pressure-sensitive adhesive layer, but may have a support. In this case, examples of the support include plastic films such as polystyrene, styrene-acrylic copolymer, acrylic resin, polyethylene terephthalate, polycarbonate, polyether ether ketone, and triacetyl cellulose; optical films such as anti-reflection films and electromagnetic wave shielding films. When the double-sided pressure-sensitive adhesive sheet has a support, the gel fraction described below indicates the gel fraction of the pressure-sensitive adhesive layer. When the double-sided pressure-sensitive adhesive sheet is a pressure-sensitive adhesive sheet composed of a pressure-sensitive adhesive layer, the double-sided pressure-sensitive adhesive sheet may be a sheet composed of a plurality of pressure-sensitive adhesive layers, but is preferably a pressure-sensitive adhesive sheet composed of a single layer of pressure-sensitive adhesive layer.
[0017] The application of the double-sided pressure-sensitive adhesive sheet of the present embodiment is not particularly limited, but it is preferably for bonding a copper mesh-based transparent conductive film since it can suppress the visualization of the copper mesh. The copper mesh preferably has a blackened film. The blackened film is a film formed by blackening treatment, in which a black coating for anti-reflection is formed on the copper mesh. Examples of the blackened film include films containing copper oxide (CuO) and copper oxynitride (CuNO). The blackened film is not particularly limited as long as it can suppress the reflectance of the copper mesh, and a known blackened film can be used, for example, a film containing a black pigment. In the blackened treatment, a copper oxide film or a copper oxynitride film can be formed on the copper mesh by sputtering or other known methods. In addition, in the blackened treatment, an electrodeposition coating of a black pigment may be applied.
[0018] Among them, the blackened film is preferably a copper oxide film or a copper oxynitride film. In this case, the double-sided pressure-sensitive adhesive sheet of the present embodiment is preferably for bonding a copper mesh-based transparent conductive film with a copper oxide film or for bonding a copper mesh-based transparent conductive film with a copper oxynitride film.
[0019] The double-sided pressure-sensitive adhesive sheet of this embodiment can also be used as a component of a general display device or optical device.
[0020] The thickness of the double-sided pressure-sensitive adhesive sheet of the present embodiment can be appropriately set according to the application, and is not particularly limited. Usually, the thickness of the double-sided pressure-sensitive adhesive sheet is preferably 10 μm or more, more preferably 20 μm or more, even more preferably 30 μm or more, and particularly preferably 40 μm or more. In addition, the thickness of the double-sided pressure-sensitive adhesive sheet is preferably 1000 μm or less, more preferably 800 μm or less, even more preferably 600 μm or less, even more preferably 500 μm or less, and particularly preferably 400 μm or less. By setting the thickness of the double-sided pressure-sensitive adhesive sheet within the above range, the oxygen permeability of the double-sided pressure-sensitive adhesive sheet is easily increased. In addition, by setting the thickness of the double-sided pressure-sensitive adhesive sheet within the above range, the step-following ability can be sufficiently ensured, and the durability can be further increased.
[0021] The total light transmittance of the double-sided pressure-sensitive adhesive sheet is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more. The total light transmittance of the double-sided pressure-sensitive adhesive sheet may be 100%. By setting the total light transmittance of the double-sided pressure-sensitive adhesive sheet within the above range, the transparency can be increased, and the sheet can be preferably used for optical applications such as display devices. The total light transmittance is a value measured in accordance with JIS K 7361-1:1997 in an environment of 23°C and relative humidity of 50%.
[0022] The haze of the double-sided pressure-sensitive adhesive sheet is preferably 5% or less, more preferably 3% or less, and even more preferably 1% or less. The lower limit of the haze value of the double-sided pressure-sensitive adhesive sheet is not particularly limited, and may be 0%. By setting the haze of the double-sided pressure-sensitive adhesive sheet within the above range, the transparency can be increased, and the sheet can be preferably used for optical applications such as display devices. The haze is a value measured in accordance with JIS K 7136:2000 in an environment of 23°C and relative humidity of 50%.
[0023] The gel fraction of the double-sided pressure-sensitive adhesive sheet is preferably 0% by mass or more, more preferably 10% by mass or more, more preferably 40% by mass or more, and particularly preferably 50% by mass or more. The gel fraction of the double-sided pressure-sensitive adhesive sheet is preferably 75% by mass or less, more preferably 70% by mass or less. By setting the gel fraction of the double-sided pressure-sensitive adhesive sheet within the above range, it becomes easier to control the oxygen permeability of the double-sided pressure-sensitive adhesive sheet within a predetermined numerical range. Furthermore, by setting the gel fraction of the double-sided pressure-sensitive adhesive sheet within the above range, the step-following ability can be improved.
[0024] The adhesive strength of the double-sided pressure-sensitive adhesive sheet to glass is preferably 2N / 10mm or more, more preferably 5N / 10mm or more. The adhesive strength of the double-sided pressure-sensitive adhesive sheet to glass is preferably 25N / 10mm or less, more preferably 20N / 10mm or less. By making the adhesive strength of the double-sided pressure-sensitive adhesive sheet to glass greater than the above range, unintended peeling does not occur, and by making it less than the above range, it can be easily peeled off when it is mistakenly attached or when the panel is disassembled for recycling. The adhesive strength of the double-sided pressure-sensitive adhesive sheet described above is a value of the adhesive strength to glass measured in accordance with the adhesive strength measurement method specified in JIS Z 0237, using a 100 μm thick polyethylene terephthalate (PET) film backed on one side of the double-sided pressure-sensitive adhesive sheet and soda glass as an adherend.
[0025] (Adhesive composition) The double-sided pressure-sensitive adhesive sheet of this embodiment is formed from a pressure-sensitive adhesive composition including a (meth)acrylic copolymer (A), a monofunctional (meth)acrylic acid ester monomer (B1) having a linear, branched or cyclic alkyl group having 10 to 20 carbon atoms, a bifunctional (meth)acrylic acid ester monomer (B2) having a reactive functional group linked by a linking group derived from a linear diol having 4 to 12 carbon atoms, and a photopolymerization initiator (C) excluding hydrogen abstraction type polymerization initiators.
[0026] ((Meth)acrylic copolymer (A)) The (meth)acrylic copolymer (A) preferably has a transparency that does not reduce the visibility of a display device, and preferably has a unit derived from a (meth)acrylate. In this specification, the term "unit" refers to a repeating unit (monomer unit) that constitutes a polymer.
[0027] The (meth)acrylic copolymer (A) preferably contains (a1) a unit derived from an acrylate having a linear or branched alkyl group having 1 to 10 carbon atoms, (a2) a unit derived from a methacrylate having a linear or branched alkyl group having 1 to 10 carbon atoms, and (a3) a unit derived from a hydroxyl group-containing (meth)acrylate. The content of (a1) the unit derived from an acrylate having a linear or branched alkyl group having 1 to 10 carbon atoms is preferably 15 to 79.5 mass%, the content of (a2) the unit derived from a methacrylate having a linear or branched alkyl group having 1 to 10 carbon atoms is preferably 20 to 79.5 mass%, and the content of (a3) the unit derived from a hydroxyl group-containing (meth)acrylate is preferably 0.5 to 15 mass% relative to the total mass of the (meth)acrylic copolymer. In this embodiment, by using a (meth)acrylic copolymer having a specific structural unit, it becomes easy to set the oxygen permeability of the double-sided pressure-sensitive adhesive sheet to a predetermined value or more. This makes it difficult for the blackened film on the copper mesh of the transparent conductive film to be reduced, and discoloration can be effectively suppressed. In addition, in this embodiment, the cohesive force of the adhesive is increased by using a (meth)acrylic copolymer having a specific structural unit, and an adhesive sheet having excellent adhesive properties and durability can be obtained.
[0028] -(a1) a unit derived from an acrylate having a linear or branched alkyl group having 1 to 10 carbon atoms- (a1) Examples of acrylates having a linear or branched alkyl group having 1 to 10 carbon atoms include methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, sec-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, pentyl acrylate, hexyl acrylate, octyl acrylate, isooctyl acrylate, isononyl acrylate, isodecyl acrylate, and 2-ethylhexyl acrylate. These may be used alone or in combination of two or more. Among them, the (meth)acrylic copolymer preferably has a unit derived from an acrylate having a branched alkyl group having 1 to 10 carbon atoms, and more preferably has a unit derived from an acrylate having a branched alkyl group having 4 to 10 carbon atoms. As the unit derived from an acrylate having such a branched alkyl group, it is preferable to have a unit derived from 2-ethylhexyl acrylate (2EHA). In addition, in this embodiment, the (meth)acrylic copolymer also preferably contains units derived from an acrylate having a branched alkyl group having 1 to 10 carbon atoms and units derived from an acrylate having a linear alkyl group having 1 to 10 carbon atoms, and more preferably contains units derived from an acrylate having a branched alkyl group having 4 to 10 carbon atoms and units derived from an acrylate having a linear alkyl group having 1 to 5 carbon atoms.
[0029] The content of (a1) units derived from an acrylate having a linear or branched alkyl group with 1 to 10 carbon atoms is preferably 15% by mass or more, more preferably 20% by mass or more, based on the total mass of the (meth)acrylic copolymer. The content of (a1) units derived from an acrylate having a linear or branched alkyl group with 1 to 10 carbon atoms is preferably 79.5% by mass, more preferably 70% by mass or less, based on the total mass of the (meth)acrylic copolymer. By setting the content of (a1) units derived from an acrylate having a linear or branched alkyl group with 1 to 10 carbon atoms within the above range, it is possible to obtain a pressure-sensitive adhesive sheet that can exhibit excellent adhesive strength and have an oxygen permeability of a predetermined value or more, thereby suppressing visualization of the copper mesh.
[0030] -(a2) a unit derived from a methacrylate having a linear or branched alkyl group having 1 to 10 carbon atoms- (a2) Examples of methacrylates having a linear or branched alkyl group having 1 to 10 carbon atoms include methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, sec-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, pentyl methacrylate, hexyl methacrylate, octyl methacrylate, isooctyl methacrylate, isononyl methacrylate, isodecyl methacrylate, and 2-ethylhexyl methacrylate. These may be used alone or in combination of two or more. Among them, the (meth)acrylic copolymer preferably has a unit derived from a methacrylate having a branched alkyl group having 1 to 10 carbon atoms, and more preferably has a unit derived from a methacrylate having a branched alkyl group having 4 to 10 carbon atoms. As the unit derived from such a methacrylate having a branched alkyl group, it is preferable to have a unit derived from 2-ethylhexyl methacrylate (2EHMA). In addition, in this embodiment, the (meth)acrylic copolymer also preferably contains units derived from a methacrylate having a branched alkyl group having 1 to 10 carbon atoms and units derived from a methacrylate having a linear alkyl group having 1 to 10 carbon atoms, and more preferably contains units derived from a methacrylate having a branched alkyl group having 4 to 10 carbon atoms and units derived from a methacrylate having a linear alkyl group having 1 to 5 carbon atoms.
[0031] It is preferable that the alkyl groups in (a1) the acrylate having a linear or branched alkyl group with 1 to 10 carbon atoms and (a2) the methacrylate having a linear or branched alkyl group with 1 to 10 carbon atoms are the same type.
[0032] The content of (a2) units derived from methacrylate having a linear or branched alkyl group having 1 to 10 carbon atoms is preferably 20% by mass or more, more preferably 25% by mass or more, based on the total mass of the (meth)acrylic copolymer. The content of (a2) units derived from methacrylate having a linear or branched alkyl group having 1 to 10 carbon atoms is preferably 79.5% by mass or more, more preferably 75% by mass or less, based on the total mass of the (meth)acrylic copolymer. By setting the content of (a2) units derived from methacrylate having a linear or branched alkyl group having 1 to 10 carbon atoms within the above range, it is possible to obtain a pressure-sensitive adhesive sheet that can exhibit excellent adhesive strength, have an oxygen permeability of a predetermined value or more, and suppress visualization of the copper mesh.
[0033] -(a3) Units derived from hydroxyl group-containing (meth)acrylate- (a3) Examples of hydroxyl group-containing (meth)acrylates include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, and polyalkylene glycol mono(meth)acrylate. These may be used alone or in combination of two or more. Among them, at least one selected from 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate is preferably used.
[0034] The content of the units derived from (a3) hydroxyl group-containing (meth)acrylate is preferably 0.5% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, based on the total mass of the (meth)acrylic copolymer. The content of the units derived from (a3) hydroxyl group-containing (meth)acrylate is preferably 15% by mass or less, more preferably 13% by mass or less, based on the total mass of the (meth)acrylic copolymer. By setting the content of the units derived from (a3) hydroxyl group-containing (meth)acrylate within the above range, excellent adhesive strength can be exhibited, and the oxygen permeability and gel fraction of the adhesive sheet can be easily controlled.
[0035] -Other monomer units- The (meth)acrylic copolymer may have other monomer units in addition to those mentioned above. Examples of the other monomers include (meth)acrylic acid ester units having a cyclic group such as cyclohexyl (meth)acrylate and benzyl (meth)acrylate, (meth)acrylonitrile, vinyl acetate, styrene, vinyl chloride, vinylpyrrolidone, and vinylpyridine. The content of the other monomer units in the (meth)acrylic copolymer is preferably 20% by mass or less, more preferably 10% by mass or less, and particularly preferably 5% by mass or less.
[0036] -Physical properties of (meth)acrylic copolymer- The weight average molecular weight of the (meth)acrylic copolymer is preferably 100,000 or more, more preferably 200,000 or more. The weight average molecular weight of the (meth)acrylic copolymer is preferably 3,000,000 or less, more preferably 2,000,000 or less. By setting the weight average molecular weight within the above range, it becomes easier to control the oxygen permeability of the pressure-sensitive adhesive sheet to a predetermined value or more, and sufficient step-following ability can be ensured. The weight average molecular weight of the (meth)acrylic copolymer is the weight average molecular weight of the (meth)acrylic copolymer contained in the pressure-sensitive adhesive composition. The weight average molecular weight is a value measured by gel permeation chromatography (GPC) and calculated based on polystyrene standard.
[0037] (Monofunctional (meth)acrylic acid ester monomer (B1)) The monofunctional (meth)acrylic acid ester monomer (B1) is a monomer having one reactive double bond in the molecule, and is a monomer having a linear, branched or cyclic alkyl group having a carbon number of 10 to 20. Examples of the monofunctional (meth)acrylic acid ester monomer (B1) having a linear, branched or cyclic alkyl group having a carbon number of 10 to 20 include isobornyl (meth)acrylate, isostearyl (meth)acrylate, stearyl acrylate (meth)acrylate, lauryl (meth)acrylate, isodecyl (meth)acrylate, cetyl (meth)acrylate, isomyristyl (meth)acrylate, undeca(meth)acrylate, tridecyl (meth)acrylate, dicyclopentanyl (meth)acrylate, and the like. Among them, the monofunctional (meth)acrylic acid ester monomer (B1) is preferably at least one selected from the group consisting of isobornyl (meth)acrylate, isostearyl (meth)acrylate, and lauryl (meth)acrylate. Commercially available examples of the monofunctional (meth)acrylic acid ester monomer (B1) include IBXA manufactured by Osaka Organic Chemical Industry Co., Ltd., ISTA manufactured by Osaka Organic Chemical Industry Co., Ltd., and LA manufactured by Osaka Organic Chemical Industry Co., Ltd.
[0038] In this embodiment, by using a monomer having a carbon number within a predetermined range as the monofunctional (meth)acrylic acid ester monomer (B1), the crosslink density of the polymer in the double-sided pressure-sensitive adhesive sheet can be controlled, and a network structure that is not dense can be formed. This allows the oxygen permeability of the double-sided pressure-sensitive adhesive sheet to be within a predetermined range, and as a result, discoloration of the blackened film of the copper mesh can be suppressed, and the visualization of the copper mesh can be suppressed.
[0039] In the pressure-sensitive adhesive composition, the content of the monofunctional (meth)acrylic acid ester monomer (B1) relative to 100 parts by mass of the (meth)acrylic copolymer (A) is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1 part by mass or more. The content of the monofunctional (meth)acrylic acid ester monomer (B1) is preferably 10 parts by mass or less. By setting the content of the monofunctional (meth)acrylic acid ester monomer (B1) within the above range, the oxygen permeability of the double-sided pressure-sensitive adhesive sheet can be set within a predetermined range, and as a result, discoloration of the blackened film of the copper mesh can be suppressed, and visualization of the copper mesh can be suppressed.
[0040] (Bifunctional (meth)acrylic acid ester monomer (B2)) The bifunctional (meth)acrylic acid ester monomer (B2) has two reactive functional groups. The two reactive functional groups are linked by a linking group derived from a linear diol having 4 to 12 carbon atoms. The two reactive functional groups are more preferably linked by a linking group derived from a linear diol having 6 to 12 carbon atoms, and even more preferably linked by a linking group derived from a linear diol having 6 to 10 carbon atoms.
[0041] The difunctional (meth)acrylic acid ester monomer (B2) is preferably represented by the following structural formula: [ka]
[0042] In the above formula, R1 and R2 are each independently a hydrogen atom or a methyl group, and preferably a hydrogen atom. R is a linear alkylene group having 4 to 12 carbon atoms, and R is preferably an alkylene group having 6 to 12 carbon atoms, and more preferably an alkylene group having 6 to 10 carbon atoms.
[0043] Examples of the bifunctional (meth)acrylic acid ester monomer (B2) in which a reactive functional group is linked by a linking group derived from a linear diol having 4 to 12 carbon atoms include 1,6-hexanediol diacrylate, 1,9-nonanediol diacrylate, and 1,10-decanediol diacrylate. Among them, the bifunctional (meth)acrylic acid ester monomer (B2) is preferably at least one selected from the group consisting of 1,6-hexanediol diacrylate and 1,10-decanediol diacrylate. Examples of commercially available products of the bifunctional (meth)acrylic acid ester monomer (B2) include A-HD-N, A-NOD-N, and A-DOD-N manufactured by Shin-Nakamura Chemical Co., Ltd.
[0044] In this embodiment, the oxygen permeability (P A ) can be easily controlled to a predetermined level, and as a result, when an adhesive sheet is attached to a copper mesh-based transparent conductive film, visualization of the copper mesh can be effectively suppressed. This is believed to be because the flexibility of the base polymer, the (meth)acrylic copolymer (A), can be increased by linking the two reactive functional groups with a linear diol having 4 to 12 carbon atoms, which has high structural flexibility.
[0045] In this embodiment, by using the bifunctional (meth)acrylic acid ester monomer (B2) as described above, the crosslink density of the polymer in the double-sided pressure-sensitive adhesive sheet can be controlled, and a network structure that is not dense can be formed. This allows the oxygen permeability of the double-sided pressure-sensitive adhesive sheet to be within a predetermined range, and as a result, discoloration of the blackened film of the copper mesh can be suppressed, and the visualization of the copper mesh can be suppressed.
[0046] In the pressure-sensitive adhesive composition, the content of the bifunctional (meth)acrylic acid ester monomer (B2) relative to 100 parts by mass of the (meth)acrylic copolymer (A) is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.2 parts by mass or more. The content of the bifunctional (meth)acrylic acid ester monomer (B2) is preferably 5 parts by mass or less. By setting the content of the bifunctional (meth)acrylic acid ester monomer (B2) within the above range, the oxygen permeability of the double-sided pressure-sensitive adhesive sheet can be set within a predetermined range, and as a result, discoloration of the blackened film of the copper mesh can be suppressed, and visualization of the copper mesh can be suppressed.
[0047] (Photopolymerization initiator (C)) The photopolymerization initiator (C) initiates the polymerization of the polyfunctional monomer by irradiation with active energy rays. Here, the term "active energy rays" refers to electromagnetic waves or charged particle rays that have an energy quantum, and examples of such rays include ultraviolet rays, electron beams, visible light, X-rays, and ion beams. Among these, from the viewpoint of versatility, ultraviolet rays or electron beams are preferred, and ultraviolet rays are particularly preferred.
[0048] The photopolymerization initiator (C) used in this embodiment is a photopolymerization initiator other than a hydrogen abstraction type polymerization initiator. By using a photopolymerization initiator other than a hydrogen abstraction type polymerization initiator, discoloration of the blackened layer can be more effectively suppressed.
[0049] Examples of the photopolymerization initiator (C) include acetophenone-based photopolymerization initiators such as 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexyl-phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropanone, 1-[4-(2-hydroxyethoxyl)-phenyl]-2-hydroxy-methylpropanone, and 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl)-2-methyl-1-propanone; acylphosphine oxide-based photopolymerization initiators such as 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and 2,4,6-trimethylbenzoyl)phenylphosphine oxide; and oil-soluble polymerization initiators such as oxime ester-based photopolymerization initiators and cationic photopolymerization initiators. Among them, the photopolymerization initiator is preferably at least one selected from the group consisting of hydroxyalkylphenone-based photopolymerization initiators and acylphosphine oxide-based photopolymerization initiators.
[0050] Commercially available photopolymerization initiators (C) include Omnirad819 and Omnirad184 manufactured by IGM Resins BV.
[0051] The content of the photopolymerization initiator (C) in the pressure-sensitive adhesive composition is preferably 0.01 parts by mass or more, and more preferably 0.05 parts by mass or more, relative to 100 parts by mass of the (meth)acrylic copolymer. The content of the photopolymerization initiator (C) in the pressure-sensitive adhesive composition is preferably 10 parts by mass or less, and more preferably 5 parts by mass or less, relative to 100 parts by mass of the (meth)acrylic copolymer. By setting the content of the photopolymerization initiator within the above range, the hardness of the double-sided pressure-sensitive adhesive sheet can be increased, and the durability, processability, and adhesion of the double-sided pressure-sensitive adhesive sheet can be improved.
[0052] (solvent) The pressure-sensitive adhesive composition may further contain a solvent. The solvent is used to improve the coatability of the pressure-sensitive adhesive composition.
[0053] Examples of such solvents include hydrocarbons such as hexane, heptane, octane, toluene, xylene, ethylbenzene, cyclohexane, and methylcyclohexane; halogenated hydrocarbons such as dichloromethane, trichloroethane, trichloroethylene, tetrachloroethylene, and dichloropropane; alcohols such as methanol, ethanol, propanol, isopropyl alcohol, butanol, isobutyl alcohol, and diacetone alcohol; ethers such as diethyl ether, diisopropyl ether, dioxane, and tetrahydrofuran; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, isophorone, and cyclohexanone; esters such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, amyl acetate, and ethyl butyrate; and polyols such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, propylene glycol monoethyl ether, and propylene glycol monomethyl ether acetate, and derivatives thereof.
[0054] The solvent may be used alone or in combination of two or more. The content of the solvent in the pressure-sensitive adhesive composition is not particularly limited, but may be 25 parts by mass or more and 500 parts by mass or less, or 30 parts by mass or more and 400 parts by mass or less, relative to 100 parts by mass of the (meth)acrylic copolymer. The content of the solvent may be 10% by mass or more and 90% by mass or less, or 20% by mass or more and 80% by mass or less, relative to the total mass of the pressure-sensitive adhesive composition.
[0055] (optional ingredient) In this embodiment, the adhesive composition may contain optional components as listed below depending on the application and required properties. However, it is preferable that the adhesive composition does not substantially contain a crosslinking agent. Specifically, the content of the crosslinking agent in the adhesive composition is preferably 0.1 mass % or less. If the content of the crosslinking agent in the adhesive composition is within the above range, it can be said that the adhesive composition does not substantially contain a crosslinking agent.
[0056] Examples of the optional components include a silane coupling agent, a plasticizer, an antioxidant, a metal corrosion inhibitor, a tackifier, a polymerization initiator, a polymerizable monomer, an ultraviolet absorber, etc. In this case, the content of the optional components is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, even more preferably 1 part by mass or less, still more preferably 0.5 parts by mass or less, and particularly preferably 0.1 parts by mass or less, relative to 100 parts by mass of the (meth)acrylic copolymer.
[0057] As the silane coupling agent, for example, a reactive functional group-containing silane coupling agent can be used. For example, mercapto-based silane coupling agents, (meth)acrylic silane coupling agents, isocyanate-based silane coupling agents, epoxy-based silane coupling agents, amino-based silane coupling agents, etc. can be mentioned. As the mercapto-based silane coupling agent, mercaptoalkoxysilane compounds (for example, mercapto group-substituted alkoxy oligomers, etc.) can be mentioned, but it is necessary to pay attention to the content as described later. As other reactive functional group-containing silane coupling agents, those described in
[0094] to
[0096] of JP 2020-114914 A can be mentioned.
[0058] The plasticizer may include, for example, a non-functional acrylic polymer. Examples of the antioxidant include phenol-based antioxidants, amine-based antioxidants, lactone-based antioxidants, phosphorus-based antioxidants, and sulfur-based antioxidants. The metal corrosion inhibitor may include a benzotriazole-based resin. Examples of the tackifier include rosin-based resins, terpene-based resins, terpene-phenol-based resins, coumarone-indene-based resins, styrene-based resins, xylene-based resins, phenol-based resins, petroleum resins, and methacrylic resins. Examples of the ultraviolet absorbing agent include benzotriazole-based compounds and benzophenone-based compounds.
[0059] It is also preferred that the pressure-sensitive adhesive composition of the present embodiment does not contain any of the optional components described above, and contains, as solid contents, only the (meth)acrylic copolymer (A), a monofunctional (meth)acrylic acid ester monomer (B1) having a linear, branched or cyclic alkyl group having 10 to 20 carbon atoms, a bifunctional (meth)acrylic acid ester monomer (B2) having a reactive functional group linked by a linking group derived from a linear diol having 4 to 12 carbon atoms, and a photopolymerization initiator (C) excluding a hydrogen abstraction type polymerization initiator.
[0060] (Double-sided adhesive sheet with release sheet) A release sheet is preferably attached to at least one surface of the double-sided pressure-sensitive adhesive sheet of this embodiment. This embodiment also relates to a double-sided pressure-sensitive adhesive sheet with a release sheet. The release sheet is peeled off from the double-sided pressure-sensitive adhesive sheet when the double-sided pressure-sensitive adhesive sheet is used.
[0061] Fig. 1 is a cross-sectional view showing an example of the configuration of a double-sided adhesive sheet with a release sheet. The double-sided adhesive sheet 1 shown in Fig. 1 has release sheets 12 (12a, 12b) on both sides of an adhesive layer 11. The double-sided adhesive sheet in Fig. 1 is a non-carrier type single-layer adhesive sheet, and is a double-sided adhesive sheet.
[0062] Examples of the release sheet include a release laminate sheet having a release sheet substrate and a release agent layer provided on one side of the release sheet substrate, or a polyolefin film such as a polyethylene film or polypropylene film as a low polar substrate. In the release laminate sheet, paper or polymer film is used as the substrate for the release sheet. As the release agent constituting the release agent layer, for example, a general-purpose addition type or condensation type silicone-based release agent or a long-chain alkyl group-containing compound is used. In particular, an addition type silicone-based release agent having high reactivity is preferably used. Specific examples of silicone-based release agents include BY24-4527 and SD-7220 manufactured by Toray Dow Corning Silicone Co., Ltd., and KS-3600, KS-774, and X62-2600 manufactured by Shin-Etsu Chemical Co., Ltd. In addition, the silicone-based release agent may contain SiO2 units and (CH3)3SiO 1 / 2 Unit or CH2=CH(CH3)SiO 1 / 2 It is preferable that the silicone resin contains a silicone resin, which is an organosilicon compound having a unit. Specific examples of the silicone resin include BY24-843, SD-7292, SHR-1404, etc. manufactured by Dow Corning Toray Silicone Co., Ltd., and KS-3800, X92-183, etc. manufactured by Shin-Etsu Chemical Co., Ltd.
[0063] In the release sheet 12, it is preferable that the release properties of the release sheets 12a and 12b are different to facilitate peeling. In other words, if the releasability from one side is different from the releasability from the other side, it becomes easy to peel off only the release sheet 12 with the higher releasability first. In this case, the releasability of the release sheet 12 between the release sheet 12a and the release sheet 12b may be adjusted according to the lamination method and the lamination order.
[0064] (Method of manufacturing double-sided pressure-sensitive adhesive sheet) The manufacturing process of the double-sided pressure-sensitive adhesive sheet of the present embodiment preferably includes a step of applying a pressure-sensitive adhesive composition onto a release sheet to form a coating film. Hereinafter, the step of applying a pressure-sensitive adhesive composition onto a release sheet to form a coating film will be described as a representative example.
[0065] The pressure-sensitive adhesive composition forming the pressure-sensitive adhesive sheet can be applied using a known coating device. Examples of the coating device include a blade coater, an air knife coater, a roll coater, a bar coater, a gravure coater, a microgravure coater, a rod blade coater, a lip coater, a die coater, and a curtain coater. The coating film can be heated using a known heating device such as a heating furnace or an infrared lamp.
[0066] In this embodiment, a step of photocuring the coating film is included. That is, the double-sided pressure-sensitive adhesive sheet of this embodiment is a photocurable double-sided pressure-sensitive adhesive sheet. Examples of light used for the light irradiation include ultraviolet light and visible light. Of these, it is preferable to use ultraviolet light having a wavelength of 250 to 400 nm. The ultraviolet light irradiation conditions are an irradiance of 0.1 mW / cm when measured with an ultraviolet illuminometer having a spectral sensitivity centered on a wavelength of 365 nm. 2 The light intensity is 500mJ / cm 2 The above is desirable. By adopting such ultraviolet irradiation conditions, a pressure-sensitive adhesive sheet with a high gel fraction and excellent durability can be obtained. As the light source, a chemical lamp, a black lamp, or other ultraviolet fluorescent lamp, a high-pressure mercury lamp, a low-pressure mercury lamp, an ultra-high-pressure mercury lamp, a mercury xenon lamp, a metal halide lamp, an LED lamp, a carbon arc, a xenon arc, or the like can be used.
[0067] In the process of photocuring the coating, the cumulative amount of ultraviolet light irradiated is 500 mJ / cm 2 More preferably, 1000 mJ / cm 2 More preferably, it is 1500 mJ / cm or more. 2 It is more preferable that the cumulative amount of ultraviolet light irradiated is 20,000 mJ / cm or more. 2 It is preferable that:
[0068] The double-sided pressure-sensitive adhesive sheet of this embodiment is completely cured by a photocuring process. The cumulative amount of ultraviolet light required for complete curing varies depending on the components contained in the pressure-sensitive adhesive composition. For example, the cumulative amount of ultraviolet light irradiated is 3000 mJ / cm. 2 That is, the double-sided pressure-sensitive adhesive sheet of the present embodiment is prepared by applying an integrated light dose of 3000 mJ / cm to a pressure-sensitive adhesive composition including a (meth)acrylic copolymer (A), a monofunctional (meth)acrylic acid ester monomer (B1) having a linear, branched or cyclic alkyl group having 10 to 20 carbon atoms, a bifunctional (meth)acrylic acid ester monomer (B2) having a reactive functional group linked by a linking group derived from a linear diol having 4 to 12 carbon atoms, and a photopolymerization initiator (C) other than a hydrogen abstraction type polymerization initiator. 2This double-sided pressure-sensitive adhesive sheet is photocured by irradiating it with ultraviolet light so that the adhesive becomes
[0069] Before the step of photocuring the coating film, a step of drying the coating film may be provided as necessary. The temperature in the drying step is preferably 50° C. or higher, more preferably 60° C. or higher, and even more preferably 70° C. or higher. The temperature in the drying step is preferably 150° C. or lower. The processing time in the drying step is preferably 10 seconds or longer, more preferably 1 minute or longer. The processing time in the drying step is preferably 1 hour or shorter.
[0070] (How to use the adhesive sheet) In the method of using the double-sided pressure-sensitive adhesive sheet of this embodiment, one release sheet of the double-sided pressure-sensitive adhesive sheet with a release sheet is peeled off and brought into contact with a copper mesh-based transparent conductive film for bonding, and then the other release sheet is peeled off and brought into contact with another adherend. If the pressure-sensitive adhesive sheet is a semi-cured pressure-sensitive adhesive sheet containing a polymerization initiator and having post-curing properties, the pressure-sensitive adhesive layer may be completely cured by irradiating it with active energy rays in this state.
[0071] (Laminate / display device) This embodiment may relate to a laminate comprising the above-mentioned double-sided adhesive sheet and a copper mesh-based transparent conductive film. For example, in the laminate of this embodiment, it is preferable that a copper mesh-based transparent conductive film is laminated on one side of the double-sided adhesive sheet, and another adherend is laminated on the other side of the double-sided adhesive sheet. It is preferable that the double-sided adhesive sheet is directly attached to the surface of the copper mesh-based transparent conductive film on which the copper mesh is formed.
[0072] This embodiment may relate to a display device including the above-mentioned double-sided adhesive sheet and a copper mesh-based transparent conductive film. For example, in the display device of this embodiment, it is preferable that a copper mesh-based transparent conductive film is laminated on one side of the double-sided adhesive sheet, and another adherend is laminated on the other side of the double-sided adhesive sheet. It is preferable that the double-sided adhesive sheet is directly attached to the surface of the copper mesh-based transparent conductive film on which the copper mesh is formed.
[0073] Other adherends include, for example, optical members constituting a display device, and examples of optical members include each component of an optical product such as a touch panel or image display device. Examples of components of a touch panel include a hard coat film, a fingerprint-resistant film, and a cover film. Examples of components of an image display device include an anti-reflection film, an orientation film, a polarizing film, a retardation film, and a brightness improvement film used in a liquid crystal display device. Examples of materials used for these members include glass, polycarbonate, polyethylene terephthalate, polymethyl methacrylate, polyethylene naphthalate, cycloolefin polymer, triacetyl cellulose, polyimide, and cellulose acylate.
[0074] [Method of manufacturing laminate] The method for producing the laminate of the present embodiment preferably includes a step of applying pressure to the surface of the copper mesh-based transparent conductive film that is in contact with the copper mesh with the double-sided pressure-sensitive adhesive sheet of the present embodiment. In this case, defoaming may be performed by applying pressure, or a defoaming step may be provided before or after the pressurizing step. The pressurizing step may be performed while heating, or a heating step may be provided before or after the pressurizing step. For example, the double-sided pressure-sensitive adhesive sheet may be brought into contact with the copper mesh-based transparent conductive film, and in this state, pressure, heating, and defoaming may be performed using an autoclave or the like, or pressure and vacuum defoaming may be performed in this state to improve adhesion. EXAMPLES
[0075] The features of the present invention will be described in more detail below with reference to examples and comparative examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the specific examples shown below.
[0076] [Synthesis example] <Synthesis of (meth)acrylic copolymer A-1> 2-Ethylhexyl acrylate (2EHA) as an acrylate having a branched alkyl group with 1 to 10 carbon atoms, 2-ethylhexyl methacrylate (2EHMA) as a methacrylate having a branched alkyl group with 1 to 10 carbon atoms, and 2-hydroxyethyl methacrylate (2HEMA) as a hydroxyl group-containing (meth)acrylate were mixed in a mass ratio of 2EHA:2EHMA:2HEMA=20:70:10, and polymerized in the presence of AIBN (azobisisobutyronitrile) in ethyl acetate as a polymerization solvent by heating to 60°C. As a result, a solution (a-1) containing a crosslinkable (meth)acrylic copolymer (A-1) with a solid content concentration of 50 mass% and a weight average molecular weight of 480,000 was obtained.
[0077] <Synthesis of (meth)acrylic copolymer A-2> Methyl acrylate (MA) and 2-ethylhexyl acrylate (2EHA) as acrylates having a linear or branched alkyl group with 1 to 10 carbon atoms, 2-ethylhexyl methacrylate (2EHMA) as methacrylates having a branched alkyl group with 1 to 10 carbon atoms, and 2-hydroxyethyl acrylate (2HEA) as hydroxyl group-containing (meth)acrylate were mixed in a mass ratio of MA:2EHA:2EHMA:2HEA=30:35:25:10, and polymerized in the presence of AIBN (azobisisobutyronitrile) in ethyl acetate as a polymerization solvent at 60°C. As a result, a solution (a-2) containing a crosslinkable (meth)acrylic copolymer (A-2) with a solid content concentration of 50 mass% and a weight average molecular weight of 800,000 was obtained.
[0078] <Synthesis of (meth)acrylic copolymer A-3> 2-Ethylhexyl acrylate (2EHA) as an acrylate having a branched alkyl group with 1 to 10 carbon atoms, methyl methacrylate (MMA) and 2-ethylhexyl methacrylate (2EHMA) as methacrylates having linear and branched alkyl groups with 1 to 10 carbon atoms, and 2-hydroxyethyl acrylate (2HEA) as a hydroxyl group-containing (meth)acrylate were mixed in a mass ratio of 2EHA:MMA:2EHMA:2HEA=20:10:60:10, and polymerized in ethyl acetate as a polymerization solvent in the presence of AIBN (azobisisobutyronitrile) by heating to 60°C. As a result, a solution (a-3) containing a crosslinkable (meth)acrylic copolymer (A-3) with a solid content concentration of 50 mass% and a weight average molecular weight of 400,000 was obtained.
[0079] <Synthesis of (meth)acrylic copolymer A-4> Butyl acrylate (BA) as an acrylate having a linear alkyl group with 1 to 10 carbon atoms, and 2-hydroxyethyl acrylate (2HEA) as a hydroxyl group-containing (meth)acrylate were mixed in a mass ratio of BA:2HEA=70:30, and polymerized in the presence of AIBN (azobisisobutyronitrile) in ethyl acetate as a polymerization solvent by heating to 60°C. This produced a solution (a-4) containing a crosslinkable (meth)acrylic copolymer (A-4) with a solid content of 50 mass% and a weight average molecular weight of 500,000.
[0080] <Weight average molecular weight> The weight average molecular weight of the (meth)acrylic copolymer was measured by gel permeation chromatography (GPC) under the following conditions. Solvent: Tetrahydrofuran Column: Shodex KF801, KF803L, KF800L, KF800D (four columns made by Showa Denko K.K. were used in combination) Column temperature: 40℃ Sample concentration: 0.5% by mass Detector: RI-2031plus (JASCO) Pump: RI-2080plus (JASCO) ·Flow rate (flow rate): 0.8ml / min ·Injection volume: 10μl Calibration curve: A calibration curve was used using 10 samples of standard polystyrene (Shodex standard polystyrene, manufactured by Showa Denko K.K.) with Mw=1320 to 2,500,000.
[0081] [Example 1] <Preparation of Pressure-Sensitive Adhesive Composition> To 100 parts by mass of the (meth)acrylic copolymer (A-1) contained in the solution (a-1), 5 parts by mass of isobornyl acrylate (IBXA) as a monofunctional (meth)acrylic acid ester monomer (B1) having a cyclic alkyl group with 10 carbon atoms, 1 part by mass of 1,6-hexanediol diacrylate (A-HD-N) as a bifunctional (meth)acrylic acid ester monomer (B2) in which a reactive functional group is linked by a linking group derived from a linear diol with 6 carbon atoms, and 0.5 parts by mass of Omnirad819 (manufactured by IGM Resins BV) as a photopolymerization initiator were added, and the raw materials were added to ethyl acetate so that the concentration of the raw materials was 40% by mass, and the mixture was stirred to prepare a pressure-sensitive adhesive composition.
[0082] <Preparation of double-sided adhesive sheet> The adhesive composition prepared as described above was applied uniformly with an applicator to the surface of a 50 μm-thick polyethylene terephthalate film (first release sheet, Oji F-Tex Co., Ltd., 50RL-07(2)) equipped with a release agent layer treated with a silicone-based release agent, so that the coating thickness after drying would be 100 μm, forming a coating film. The coating film was dried at 80° C. for 3 minutes in an air-circulating thermostatic oven, forming an adhesive layer (double-sided adhesive sheet of Example 1) on the surface of the first release sheet.
[0083] <Preparation of double-sided adhesive sheet with release sheet> Next, a 38μm-thick second release sheet (Oji F-Tex Co., Ltd., 38RL-07(L)) with a different release strength from the first release sheet was attached to the surface of the adhesive layer, and cured for 14 days under conditions of 23°C and 50% relative humidity. This resulted in a double-sided adhesive sheet with release sheet, in which the adhesive layer (adhesive sheet) is sandwiched between a pair of release sheets with different release strengths (first release sheet / double-sided adhesive sheet / second release sheet configuration). Next, a high-pressure mercury lamp was used to illuminate the second release sheet side of this adhesive sheet with release sheet, with an integrated light intensity of 3000mJ / cm. 2 Thus, a photocured double-sided pressure-sensitive adhesive sheet with a release sheet was obtained.
[0084] [Example 2] A photocured double-sided pressure-sensitive adhesive sheet with a release sheet was obtained using the same procedure as in Example 1, except that the solution (a-1) of the (meth)acrylic copolymer (A-1) was changed to the solution (a-2) of the (meth)acrylic copolymer (A-2) and the isobornyl acrylate (IBXA) was changed to isostearyl acrylate (ISTA), a monofunctional (meth)acrylic acid ester monomer having a branched alkyl group having 18 carbon atoms.
[0085] [Example 3] A photocured double-sided pressure-sensitive adhesive sheet with a release sheet was obtained in the same manner as in Example 1, except that the solution (a-1) of the (meth)acrylic copolymer (A-1) was changed to the solution (a-3) of the (meth)acrylic copolymer (A-3), the isobornyl acrylate (IBXA) was changed to lauryl acrylate (LA), a monofunctional (meth)acrylic acid ester monomer having a linear alkyl group with 12 carbon atoms, and further, 1,6-hexanediol diacrylate (A-HD-N) was changed to 1,10-decanediol diacrylate (A-DOD-N), a bifunctional (meth)acrylic acid ester monomer in which a reactive functional group is linked by a linking group derived from a linear diol having 10 carbon atoms, and 0.5 parts by mass of Omnirad819 (manufactured by IGM Resins BV) was changed to 1.0 part by mass of Omnirad184 (manufactured by IGM Resins BV).
[0086] [Example 4] A photocured double-sided pressure-sensitive adhesive sheet with a release sheet was obtained using the same procedures as in Example 1, except that isobornyl acrylate (IBXA) was changed to isostearyl acrylate (ISTA), a monofunctional (meth)acrylic acid ester monomer having a branched alkyl chain with 18 carbon atoms, 1,6-hexanediol diacrylate (A-HD-N) was changed to 1,10-decanediol diacrylate (A-DOD-N), a bifunctional (meth)acrylic acid ester monomer in which a functional group is linked to a linear diol having 10 carbon atoms, and 0.5 parts by mass of Omnirad819 (manufactured by IGM Resins BV) was changed to 1.0 part by mass of Omnirad184 (manufactured by IGM Resins BV).
[0087] [Comparative Example 1] A photocured double-sided adhesive sheet with a release sheet was obtained using the same procedure as in Example 1, except that isobornyl acrylate (IBXA) was replaced with methyl acrylate (MA), a monofunctional (meth)acrylic acid ester monomer having an alkyl group with one carbon atom.
[0088] [Comparative Example 2] A photocured double-sided pressure-sensitive adhesive sheet with a release sheet was obtained using the same procedure as in Example 1, except that the solution (a-1) of base polymer (A-1) was changed to solution (a-4) of base polymer (A-4) and 1,6-hexanediol diacrylate (A-HD-N) was changed to a trifunctional acrylic acid ester monomer, trimethylolpropane triacrylate (A-TMPT).
[0089] [Comparative Example 3] A double-sided adhesive sheet with a release sheet was obtained using the same procedure as in Example 1, except that 0.5 parts by mass of an isocyanate-based crosslinking agent (D-110N, manufactured by Mitsui Chemicals) was added instead of adding a monofunctional (meth)acrylic acid ester monomer, a bifunctional (meth)acrylic acid ester monomer, and a photoinitiator.
[0090] (Evaluation and Measurement) <Oxygen permeability (P A )> [Making laminated sheets] The release sheet on the light release side of the double-sided adhesive sheet with release sheet (thickness of double-sided adhesive sheet: 100 μm) after photocuring prepared in the Examples and Comparative Examples was peeled off, and 20 μm of unstretched polypropylene (Rensol GP-32, manufactured by Hokuetsu Kasei Co., Ltd.) was attached using a hand roller to obtain an adhesive sheet backed with unstretched polypropylene. Next, the release sheet on the heavy release side of the unstretched polypropylene-backed adhesive sheet was peeled off, and the 100 μm-thick double-sided adhesive sheet prepared in the Examples and Comparative Examples was attached to the exposed adhesive surface so that the adhesive surfaces of the sheets were in contact with each other, to obtain an adhesive sheet backed with unstretched polypropylene with an adhesive layer thickness of 200 μm. Next, the release sheet on the heavy release side of the adhesive sheet backed with unstretched polypropylene with an adhesive layer thickness of 200 μm was peeled off, and 20 μm of unstretched polypropylene (Rensol GP-32, manufactured by Hokuetsu Chemicals) was laminated to the exposed adhesive surface to produce a laminated sheet with the configuration "unstretched polypropylene / adhesive layer (thickness 200 μm) / unstretched polypropylene."
[0091] [Oxygen permeability of laminated sheet (P L ) Measurement Oxygen permeability of laminated sheet (P L The oxygen permeability was measured using an oxygen permeability meter (OX-TRAN2 / 12, manufactured by MOCON) with a test cell area (measurement area) of 50 cm 2 The oxygen permeability was then measured after leaving the sample in an environment of 23°C, 50% relative humidity, and 1 atm for about 2 hours until the oxygen permeability stabilized. 2 The oxygen permeability of the laminated sheet (P L ) was calculated.
[0092] [Oxygen permeability of unstretched polypropylene (P P ) Measurement Two sheets of 20 μm thick non-oriented polypropylene film (CPP) were laminated together to a thickness of 40 μm, and the oxygen permeability (P L The oxygen permeability was measured using an oxygen permeability measuring device (OX-TRAN2 / 212, manufactured by MOCON) in the same manner as in "Measurement of oxygen permeability" above.2 The oxygen permeability of unstretched polypropylene (P P ) was calculated.
[0093] [Oxygen permeability (P A ) calculation] The oxygen permeability (P L ) and the oxygen permeability of unstretched polypropylene (P P ) was calculated using the following formula (2) derived from the following formula (1) to determine the oxygen permeability (P A ) was calculated. 1 / P L =1 / P A +1 / P P ··· Equation (1) P A =(P P ×P L ) / (P P -P L )...Equation (2)
[0094] <Suitability for copper mesh-based transparent conductive film> (Preparation of conductive film for evaluation) A transparent conductive film was prepared by providing a copper conductive layer on both sides of a 100μ polyethylene terephthalate substrate in accordance with the method described in Example 3 of Japanese Patent No. 6607918. Next, a grid-like wiring pattern with a pitch of 200μm and a line width of 15μm was formed on the conductive parts on both sides of this conductive film using a photolithography technique to prepare a copper mesh-based transparent conductive film for evaluation. Then, a blackened film was formed on the copper mesh in accordance with the method described in Example 3 of Japanese Patent No. 6607918.
[0095] (Preparation of evaluation samples) The release sheet on the light release side of the double-sided adhesive sheet with release sheet prepared in the examples and comparative examples was peeled off, and the sheet was attached to one side of a glass slide (Matsunami Glass Co., Ltd., S9112) using a hand roller. Next, the release sheet on the heavy release side of the adhesive sheet backed with glass was peeled off, and the sheet was attached to the copper mesh-based transparent conductive film for evaluation prepared above. Next, the double-sided adhesive sheet prepared in the examples and comparative examples was attached to the surface of the copper mesh-based transparent conductive film of the laminate having the configuration of "glass / adhesive layer / copper mesh-based transparent conductive film". Next, the release sheet on the heavy release side was peeled off, and a glass slide (Matsunami Glass Co., Ltd., S9112) was attached using a vacuum laminating device (JE2020B-MVH type, Joyo Engineering Co., Ltd.) to prepare a laminate of "glass / adhesive layer / copper mesh-based transparent conductive film / adhesive layer / glass". Next, the laminate was autoclaved for 30 minutes at 50°C and 0.5 MPa. Thereafter, the plate was left for 24 hours under conditions of 23° C. and 50% relative humidity to prepare a sample for evaluating the suitability of the copper mesh-based transparent conductive film.
[0096] (Evaluation of suitability of copper mesh-based transparent conductive film) The copper mesh-based transparent conductive film suitability evaluation samples prepared above were treated in an oven at 95°C for 250 hours. After that, the appearance of the evaluation samples was visually observed, and the wiring parts were observed under an optical microscope, and the copper mesh-based transparent conductive film suitability was evaluated based on the following evaluation criteria. No floating, peeling, or air bubbles were observed in any of the samples. A: The copper mesh is invisible to the naked eye. There is no color change in the wiring even when observed under a microscope. B: The copper mesh is not visible to the naked eye, but a clear change in hue can be seen in the wiring area when observed under a microscope, but the color change is uniform overall. C: The copper mesh is not visible to the naked eye, but a clear change in hue is observed in the wiring when observed under a microscope, and the hue differs between the edge and center of the sample. D: The edges of the sample appear slightly cloudy to the naked eye, and under a microscope there is a clear change in color in the wiring area. Furthermore, the edges and center of the sample have different colors. E: The copper mesh is visible to the naked eye, and microscopic observation reveals a clear change in hue and a glossy appearance in the wiring.
[0097] <Total light transmittance and haze value> The release sheet on the light release side of the double-sided adhesive sheet with release sheet (thickness of the double-sided adhesive sheet: 100 μm) prepared in the examples and comparative examples was peeled off, and the sheet was attached to one side of a slide glass (manufactured by Matsunami Glass Co., Ltd., S9112) using a hand roller, and this laminate was autoclaved for 30 minutes under conditions of 50 ° C. and 0.5 MPa. Thereafter, the release sheet on the heavy release side was peeled off to prepare an evaluation sample having a "glass / adhesive layer" configuration, and the total light transmittance of the obtained sample was measured in accordance with JIS K 7361-1. The haze value of the obtained sample was also measured in accordance with JIS K 7136. These measurements were performed three times, and the average value was taken as each measured value. An integrating sphere type light transmittance measuring device (manufactured by Nippon Denshoku Industries Co., Ltd., NDH-5000) was used for the measurement. As a result, the double-sided pressure-sensitive adhesive sheets produced in the examples and comparative examples all had a total light transmittance of 90% to 100% in an environment of 23°C and relative humidity of 50%, and a haze value of less than 1% in an environment of 23°C and relative humidity of 50%.
[0098] <Gel fraction> Approximately 0.1 g of the adhesive layer was placed in a sample bottle, 30 ml of ethyl acetate was added, and the mixture was shaken for 24 hours. The contents of the sample bottle were then filtered through a 150 mesh stainless steel wire screen, and the residue on the wire screen was dried at 100°C for 1 hour to measure the dry weight W (g). The obtained dry weight was calculated using the following formula: Gel fraction (%) = (dry mass W / collected mass of adhesive sheet) x 100 The value calculated from the above was regarded as the gel fraction of the pressure-sensitive adhesive sheet.
[0099] [Table 1]
[0100] When the double-sided pressure-sensitive adhesive sheet obtained in the examples was attached to a copper mesh-based transparent conductive film and treated under high temperature conditions, the change in hue of the wiring portion was suppressed, and the visibility of the copper mesh portion was suppressed. [Explanation of symbols]
[0101] 1 Double-sided adhesive sheet with release sheet 11 Double-sided adhesive sheet (adhesive layer) 12a, 12b Release sheet
Claims
1. A (meth)acrylic copolymer (A), a monofunctional (meth)acrylic acid ester monomer (B1) having a linear, branched or cyclic alkyl group having 10 to 20 carbon atoms; a bifunctional (meth)acrylic acid ester monomer (B2) having a reactive functional group linked via a linking group derived from a linear diol having 4 to 12 carbon atoms; A double-sided pressure-sensitive adhesive sheet obtained by photocuring a pressure-sensitive adhesive composition containing a photopolymerization initiator (C) other than a hydrogen abstraction polymerization initiator, The (meth)acrylic copolymer (A) contains (a1) units derived from an acrylate having a linear or branched alkyl group having 1 to 10 carbon atoms, (a2) units derived from a methacrylate having a linear or branched alkyl group having 1 to 10 carbon atoms, and (a3) units derived from a hydroxyl group-containing (meth)acrylate, the content of the monofunctional (meth)acrylic acid ester monomer (B1) is 0.1 to 10 parts by mass, and the content of the bifunctional (meth)acrylic acid ester monomer (B2) is 0.05 to 5 parts by mass, relative to 100 parts by mass of the (meth)acrylic copolymer (A); The oxygen permeability (P) of the double-sided PSA sheet was measured and calculated by the following measurement method. A ) is 2000ml / (m 2 - 1 day · 1 atm) or more; (Measurement method) The thickness of the double-sided pressure-sensitive adhesive sheet was set to 200 μm, and a 20 μm-thick non-oriented polypropylene film (CPP) was attached to each of both sides of the sheet to produce a laminated sheet having a layer structure of "CPP (20 μm) / double-sided sheet (pressure-sensitive adhesive layer 200 μm) / CPP (20 μm)". The amount of oxygen transmitted through the laminated sheet was measured using an oxygen transmission rate measuring device under an environment of 23° C., relative humidity 50%, and 1 atm. 2 The oxygen permeability (P L Similarly, the oxygen permeability (P P ) was calculated, and the oxygen permeability (P A ) is calculated. 1 / P L =1 / P A +1 / P P ・・・ Formula (1) P A =(P P ×P L ) / (P P -P L ) ………… Formula (2)
2. 2. The double-sided pressure-sensitive adhesive sheet according to claim 1, having a total light transmittance of 80% or more.
3. The double-sided pressure-sensitive adhesive sheet according to claim 1 , having a gel fraction of 75 mass % or less.
4. A laminate comprising the double-sided pressure-sensitive adhesive sheet according to any one of claims 1 to 3 and a copper mesh-based transparent conductive film.
5. A display device comprising the double-sided pressure-sensitive adhesive sheet according to any one of claims 1 to 3 and a copper mesh-based transparent conductive film.
Citation Information
Patent Citations
Curable pressure-sensitive adhesive composition, pressure-sensitive adhesive, and pressure-sensitive adhesive sheet
JP2014133812A
Acrylic resin composition, acrylic adhesive, adhesive sheet, double-sided adhesive sheet, adhesive for transparent electrode, touch panel and image display device, and production method of adhesive layer-containing laminate
JP2014201709A
Manufacturing method of touch panel sensor
JP2015125563A
Ultraviolet-curable adhesive composition
JP2019052213A
Conductive laminated body for touch panel, and method for manufacturing conductive laminated body for touch panel
WO2016136117A1